Reliability of fine needle aspiration biopsy in diagnosis of breast lump - Abedalrahman, Sarab K. (AL-Kindy College Medical Journal, 2019)
Background: breast cancer is commonest cancer globally and the 1st cancer in Iraq among females, its management and prognosis depend on early diagnosis, the traditional method was excisional biopsy which is expensive and invasive leading to delayed diagnosis, FNAB is cheap nom invasive more acceptable to women, Aim of the study: to test the reliability of FNAB in preoperative diagnosis of breast lump.Methodology: This is a retrospective study of 204 cases, 102 breast cancer cases and 102 benign breast lesions, taken between Jan. 2017 – Nov. 2017. The sample taken from the breast cancer early detection center in  Al-Alwiyaa maternity teaching hospital, during the year 2017Results: Invasive ductal carcinoma (IDC) was found among  82(80.4%) of malignant cases, ILC was 14(13.7%) , fibroadenoma was the most common  benign lesions 51(50%), The absolute sensitivity was 96% , specificity 100%, with 4% false negative the accuracy was 98%. The complete sensitivity was 96%, and specificity was 83%, with 4% false negative and 17% false positive cases, the accuracy was 90%,Conclusion and recommendation: fine-needle aspiration biopsy (FNAB) is accurate for breast lump diagnosis. With high sensitivity and specificity. FNAB is a good screening method and help in an improvement of treatment planning